Medicinal Plants, Phytochemicals, and Their Impacts on the Maturation of the Gastrointestinal Tract - Mukonowenzou, Nyasha Charity; Adeshina, Kehinde Ahmad; Donaldson, Janine; Ibrahim, Kasimu Ghandi; Usman, Dawoud; Erlwanger, Kennedy Honey (Frontiers in Physiology, 2021)
The gastrointestinal tract (GIT) is the first point of contact for ingested substances and thus represents a direct interface with the external environment. This interface plays a significant role in immunity and contributes to the wellbeing of individuals through the brain-gut-microbiota axis. The transition of life from the in utero environment, to suckling and subsequent weaning has to be matched by phased development and maturation of the GIT; from an amniotic fluid occupancy during gestation, to the milk in the suckling state and ultimately solid food ingestion at weaning. This phased maturation of the GIT can be affected by intrinsic and extrinsic factors, including diet. Despite the increasing dietary inclusion of medicinal plants and phytochemicals for health benefits, a dearth of studies addresses their impact on gut maturation. In this review we focus on some recent findings on the impact of medicinal plants and phytochemicals in inducing precocious maturation of the GIT, not only in humans but in pertinent animals.